CASHLESS MANAGEMENT IN ISLAMIC BOARDING SCHOOLS TO ENHANCE STUDENT’S FINANCIAL DISCIPLINE: (A CASE STUDY AT PONDOK PESANTREN IBNU HAFIZ SUBANG) - Misbahudin, R. Muhammad; Helmawati, Helmawati (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
The problems that often occur at the Ibnu Hafiz Islamic Boarding School, Subang, are related to the use of cash among students, such as losing money, wasting money, and difficulty controlling daily expenses. In response to these conditions, the Islamic boarding school implemented a cashless system based on electronic cards connected to each student's account. This study examines the cashless system's management (POAC) in improving students' financial discipline at the Ibnu Hafiz Islamic Boarding School, Subang. This study uses a qualitative approach with a case study method. Data were obtained through in-depth interviews, observations, and documentation, which were analyzed using the POAC (Planning, Organizing, Actuating, Controlling) framework. The results of the study indicate that the cashless system was planned based on real needs in the field to discipline and educate students financially. In terms of organization, the Islamic boarding school formed a special team, collaborated with banks, and conducted socialization for all elements of the Islamic boarding school. The implementation of the system was carried out in stages and systematically, accompanied by mentoring and education for students. Evaluations were carried out periodically by internal and external teams (banks and student guardians) to ensure the system's effectiveness. Implementing the cashless system has been proven to reduce violations related to money, increase discipline, and shape the character of students who are more orderly, economical, and financially responsible. In conclusion, cashless management in Islamic boarding schools has not only succeeded in overcoming technical financial problems. However, it is also effective in fostering students' character through healthy financial habits.